Recognition of features of the entrance of Pahlavi period buildings in Zahedan City - Shahrzad Teymouri; Faramarz Hassanpour; mehrpooya Hossein (تحقیقات کاربردی علوم جغرافیایی)
In this article, the aim is to Recognition the features of the entrances of Pahlavi period buildings in Zahedan and then prioritize these features. The research method is descriptive-analytical and quantitative-qualitative. Data collection in the first stage is through content analysis method based on images and researcher observations of 8 buildings in the city. In the second stage, building features were prioritized through a questionnaire tool and using AHP method. The number of experts to weigh the criteria was 10 people. The result of the research shows that the architectural style of the 8 buildings studied is the traditional architectural style; A study of the typology of the entrance of the building based on the facade decorations shows that the decorations are based on the traditional architectural style and most of the designs, shapes and inscriptions on the entrance of the building include brickwork, use of simple designs and shapes. In fact, the use of bricks and materials compatible with the climate of the region with simple designs and in many cases without designs on the entrances, is the dominant species. Therefore, the predominant type of buildings at the entrance of Zahedan city is of traditional architecture and in a simple way and decorations are also based on bricks. The result of AHP method showed that simple, truncated, snake and vein decorations weighing 0.282 are known as the most important decorative features of the entrance of the building in Zahedan. The use of simple brick inscriptions weighing 0.181 is also in the second place in terms of importance in terms of decorations on the entrance of the building.